2002
DOI: 10.1021/jp021048x
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Spontaneous Emission from the Film of Poly(aryl ether) Dendrimer Encapsulating Excited-State Intramolecular Proton Transfer Dye

Abstract: Nonresonant exponential amplification of the excited-state intramolecular proton transfer (ESIPT) emission has been investigated with the film of ESIPT dendrimer (QG2) by pico- and femtosecond laser experiments. The intrinsic four-level nature of ESIPT and the reduced concentration quenching by dendritic effect made QG2 film an optical gain medium with the threshold intensity lower than 20 μJ/cm2/pulse. The characteristics of emission amplification are discussed in terms of the amplified spontaneous emission (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Effi cient ASE of ESIPT molecule was also observed in dendrimer neat fi lms [ 88 ] and highly doped polymer fi lms. [ 89 ] The second generation poly(aryl ether) dendrimer QG2 (Figure 10 a) incorporating quinoline-based ESIPT moieties showed large Stokes' shifted ( ∼ 200 nm) orange K * emission ( ∼ 570 nm) in the neat fi lm.…”
Section: Amplifi Ed Spontaneous Emission (Ase)mentioning
confidence: 84%
See 1 more Smart Citation
“…Effi cient ASE of ESIPT molecule was also observed in dendrimer neat fi lms [ 88 ] and highly doped polymer fi lms. [ 89 ] The second generation poly(aryl ether) dendrimer QG2 (Figure 10 a) incorporating quinoline-based ESIPT moieties showed large Stokes' shifted ( ∼ 200 nm) orange K * emission ( ∼ 570 nm) in the neat fi lm.…”
Section: Amplifi Ed Spontaneous Emission (Ase)mentioning
confidence: 84%
“…[ 89 ] The second generation poly(aryl ether) dendrimer QG2 (Figure 10 a) incorporating quinoline-based ESIPT moieties showed large Stokes' shifted ( ∼ 200 nm) orange K * emission ( ∼ 570 nm) in the neat fi lm. [ 88 ] Interestingly, it was observed that the fl uorescence of QG2 solution in any good solvents was very weak but that of spin-cast fi lm was quite strong due to the RIR effect described above in the section 3.2.3. When the QG2 fi lm was excited by a 355 nm picosecond laser pulse, the orange K * emission was amplifi ed and shifted to the narrow red ASE emission at 670 ∼ 695 nm.…”
Section: Amplifi Ed Spontaneous Emission (Ase)mentioning
confidence: 99%
“…The excitedstate intramolecular proton transfer (ESIPT) attracts much attention particularly due to its dual emission with large Stokes' shift, which leads to its significant applications in molecular probes [5,[13][14][15][16], laser dyes [17][18][19], luminescent materials [20][21][22], chemosensors [23][24][25][26][27][28][29][30][31] and molecular logic gates [32], etc. Hence, the mechanism investigation of ESIPT is of vital importance to design, synthesize and regulate desired luminescent molecules [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In this area, the photoisomerization of dendrimers with photoresponsive cores-such as stilbene, [13][14][15][16][17][18][19][20][21] azobenzene, [22][23][24][25][26][27][28][29][30][31][32][33] diarylethene, [34][35][36][37][38] intramolecularly hydrogen-bonded chromophores, [39][40][41] and photolabile chromophores 42-44 -has been extensively investigated. We recently reported that stilbene dendrimers with benzyl ether-type dendrons exhibited a volume-conserving isomerization mechanism and a macromolecular effect (or generation effect) on energy transfer efficiency from the peripheral dendrons to the core stilbene in organic solvents [45][46][47] and aqueous solution.…”
Section: Introductionmentioning
confidence: 99%